PsychoBehavioroimmunology: Connecting the Behavioral Immune System to Its Physiological Foundations - Murray, Damian R.; Prokosch, Marjorie L.; Airington, Zachary (Frontiers in Psychology, 2019)
Although infectious disease has posed a significant and persistent threat to human survival and welfare throughout history, only recently have the psychological and behavioral implications of disease threat become a topic of research within the behavioral sciences. This growing body of work has revealed a suite of affective and cognitive processes that motivate the avoidance of disease-causing objects and situations—a cascade of processes loosely conceptualized as a “behavioral immune system.” Recent behavioral immune system research has linked disease threat to a surprisingly broad set of psychological and behavioral phenomena. However, research examining how the behavioral immune system is nested within our broader physiology is only beginning to emerge. Here, we review research that has begun to elucidate the physiological foundations of the behavioral immune system—at the levels of sensory modalities, cells, and genes. We also discuss the future of this work.